2021
DOI: 10.1186/s41235-021-00324-y
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and incremental predictive validity of implicit attitudes: studies of a race-based phenotype

Abstract: Four studies involving 2552 White American participants were conducted to investigate bias based on the race-based phenotype of hair texture. Specifically, we probed the existence and magnitude of bias in favor of Eurocentric (straight) over Afrocentric (curly) hair and its specificity in predicting responses to a legal decision involving the phenotype. Study 1 revealed an implicit preference, measured by an Implicit Association Test (IAT), favoring Eurocentric over Afrocentric hair texture among White America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…More recently, Kurdi et al, ( 2021 ) measured attitudes toward a phenotypic feature that happens to be a dominant perceptual marker of race, Afrocentric and Eurocentric types of hair. First participants took an IAT measuring their implicit attitude toward Black women with natural or straightened hair.…”
Section: Systemic Racial Bias: the Role Of Mental Structures And Resulting Social Interactionsmentioning
confidence: 99%
“…More recently, Kurdi et al, ( 2021 ) measured attitudes toward a phenotypic feature that happens to be a dominant perceptual marker of race, Afrocentric and Eurocentric types of hair. First participants took an IAT measuring their implicit attitude toward Black women with natural or straightened hair.…”
Section: Systemic Racial Bias: the Role Of Mental Structures And Resulting Social Interactionsmentioning
confidence: 99%
“…The best method for addressing this issue is through latent variable approaches like SEM, which account for measurement error, and simulation studies have shown strong divergences in conclusions about incremental predictive validity when comparing SEM versus multiple linear regression ( Westfall & Yarkoni, 2016 ), with only SEM being able to properly maintain Type I error rates as sample sizes increase. To date, few studies have used SEM in tests of incremental predictive validity for indirect measures (cf., Axt et al, 2020 ; Kurdi et al, 2021 ). The most in-depth examination comes from Buttrick et al (2020) where an analysis of more than 15,000 participants compared conclusions about incremental predictive validity for SEM versus multiple linear regression across 10 IATs and 250 outcome variables.…”
Section: Incremental Predictive Validitymentioning
confidence: 99%
“…To measure implicit racial attitudes, an implicit association test has been developed, to measure the difference between associations with two target concepts and attributes. Implicit and explicit bias could predict participants' relevant social behavior, and implicit racial attitude could predict the measure of intergroup behavior [10].…”
Section: Introductionmentioning
confidence: 99%